Improving Urban Water Environment in Eastern China by Blending Traditional with Modern Landscape Planning - Jiajie Cao; Junjun Yu; Yuan Tian; Cai Zhao; Hao Wang (Scientifica)
As a fundamental part of greenspace, urban water landscape contributes greatly to the ecological system and at the same time supplies a leisure area for residents. The paper did an analysis on the number of aquatic plant communities, the form of water spaces, and water quality condition by investigating 135 quadrats (90 at amphibious boundary and the land, 45 in the water) in 45 transects of 15 urban and suburban parks. We found that water spaces had monotonous forms with low biodiversity and poor water quality. In addition, urban water landscapes hardly provided ecological functions given excessive construction. Accordingly, a proposition to connect tradition with modernism in the improvement and innovation of urban water landscape planning was put forward, and further, the way to achieve it was explored. By taking Qinhu Wetland Park as a case, the principles and specific planning methods on macro- and microperspectives were discussed to guide the development of urban landscape in eastern China.